Importance of N2O in greenhouse gas budgets of tropical peatlands - Pärn, Jaan; Espenberg, Mikk; Soosaar, Kaido; Kasak, Kuno; Thayamkottu, Sandeep; Schindler, Thomas; Ranniku, Reti; Sohar, Kristina; Malaverri, Lizardo Fachín; Melling, Lulie; Mander, Ülo (Frontiers in Environmental Science, 2025)
Tropical peatland ecosystems significantly influence Earth’s climate through their greenhouse gas exchange. Permanently wet peatlands take up carbon dioxide in plants and accumulate organic carbon in soil but release methane. Man-made drainage of peat releases carbon dioxide and nitrous oxide. Exchange of the greenhouse gases in relationship with tropical conditions are poorly understood. This is a global-scale field study of fluxes of three greenhouse gases – carbon dioxide, methane and nitrous oxide – and their environmental drivers across the full moisture range of tropical peatlands. We show that net emission of carbon dioxide dominates greenhouse gas budgets in drained tropical peatlands while nitrous oxide emission is the second most important contributor. Tropical peat swamp forests in their natural wet states are large greenhouse gas sinks and should be a global conservation and restoration priority.